Personal Income and its Distribution in Spanish municipalities - Miriam Hortas-Rico; Jorge Onrubia (REGION, 2015)
This resource describes a data source for local personal income and its distribution in Spanish municipalities.
Keywords: 330; local income distribution; Personal Income Tax returns; income inequality; top incomes; Spanish municipalities; regional economics; Spain; 2002 - present; personal income